2020
DOI: 10.31620/jccc.12.20/04
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis on Job Stress Using Visualizing Network

Abstract: Job stress is the most prevalent issue of the current scenario. It is observed that one out of four employees is affected by stress; thereby, it has attained the interests of many researchers. The rapid evolution of job stress research papers in the last years resulted that there is a need to conduct a detailed analysis of literature in this field. To address this problem, some researchers published a few review papers on job stress from different perspectives. Nonetheless, papers have not been published on jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Para estos autores, se pueden crear nuevas formas de comunicación e interacciones a través de experiencias inmersivas, y desarrollar servicios y formas de entretenimiento. Shukla et al (2023) hacen un análisis bibliométrico sobre tendencias y temas del metaverso en el sector empresarial, en el que observan que el mayor crecimiento se produce en 2022 y las palabras clave más utilizadas son metaversos, realidad virtual y sostenibilidad. Agac et al (2023), en su revisión de la literatura sobre metaverso en educación sanitaria, observan que el uso de tecnologías innovadoras ofrece ventajas en coste, tiempo y experiencia.…”
Section: Resultsunclassified
See 1 more Smart Citation

La revolución del metaverso

Ramírez-Herrero,
Ortiz-de-Urbina-Criado,
Medina-Merodio
2023
esicm
“…Para estos autores, se pueden crear nuevas formas de comunicación e interacciones a través de experiencias inmersivas, y desarrollar servicios y formas de entretenimiento. Shukla et al (2023) hacen un análisis bibliométrico sobre tendencias y temas del metaverso en el sector empresarial, en el que observan que el mayor crecimiento se produce en 2022 y las palabras clave más utilizadas son metaversos, realidad virtual y sostenibilidad. Agac et al (2023), en su revisión de la literatura sobre metaverso en educación sanitaria, observan que el uso de tecnologías innovadoras ofrece ventajas en coste, tiempo y experiencia.…”
Section: Resultsunclassified
“…El mundo real y académico se plantean si hay un nuevo paradigma social con el metaverso y hay posturas a favor y en contra. En el contexto académico, hay algunas revisiones de la literatura sobre el metaverso (Agac et al, 2023;Cruz et al, 2023;Shukla et al, 2023;Wider et al, 2023) y sus aplicaciones (Chen et al, 2023;Shen et al, 2023;Tlili et al, 2022), pero se ha reflexionado poco sobre sus pros/contras.…”
Section: Introductionunclassified

La revolución del metaverso

Ramírez-Herrero,
Ortiz-de-Urbina-Criado,
Medina-Merodio
2023
esicm
“…This analysis may include mapping scientific fields, performing citation analysis to trace influence and knowledge flows, and conducting network analysis to explore relationships among authors, institutions, and countries. Techniques such as co-citation and co-authorship analysis are frequently employed to identify research clusters and collaborative patterns [ 18 ]. Overall, bibliometric methods provide an empirical foundation for comprehending the dynamics of scientific research, offering crucial insights for scholars, policymakers, and librarians alike, thereby enabling stakeholders to effectively and strategically navigate the vast landscapes of scientific output [ 19 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on metaverse is very current. It can be observed that pioneers in this topic have conducted studies to mainly define and delimit the concept [ 3 ], explore its technologies [ 5 ] and its applications in topics such as education [e.g., [ [9] , [10] , [11] ]], business management [ 12 , 13 ] marketing [ 14 , 15 ], journalism [ 16 ], the fashion industry [ 17 ] or sustainable development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The economic model of the metaverse developed from the previous IoT ecosystem implies an exchange of information and data where the user gains content while the online platforms receive a data and economic return. Every online transaction means data collection for the business that supports the platform [ 13 ]. The metaverse replicates this data process, although there are specific issues to be discussed to navigate in a secure environment.…”
Section: Introductionmentioning
confidence: 99%